Structure and agency in capabilities‐enhancing homeless services: Housing first, housing quality and consumer choice. (6th October 2021) - Greenwood, Ronni Michelle; Manning, Rachel M.; O'Shaughnessy, Branagh R.; Vargas‐Moniz, Maria J.; Auquier, Pascal; Lenzi, Michela; Wolf, Judith; Bokszczanin, Anna; Bernad, Roberto; Källmén, Håkan; Spinnewijn, Freek; Ornelas, Jose; et al.
Abstract: The capabilities approach, a framework for understanding and measuring inequality, stipulates that equality is best understood as the freedom to do and be within a particular context. Homelessness has been referred to as a situation of 'capabilities deprivation', and the extent to which homeless services restore or enhance capabilities is of increasing interest. As part of a large, eight‐country study of homelessness in Europe, we examined the extent to which adults with histories of homelessness perceived the services they receive as capabilities‐enhancing. We collected data at two time points: baseline ( n t1  = 565) and follow‐up ( n t2  = 399). Measures included perceived capabilities, choice and housing quality. Participants engaged with Housing First (HF) programmes perceived services as more capabilities‐enhancing than participants engaged with treatment as usual (TAU); this relationship was mediated by consumer choice and perceived housing quality. Implications for social policy, practice and training are discussed.